A bronchial fibroepithelial polyp with abnormal findings on auto‐fluorescence imaging. Issue 5 (9th June 2017) - Saito, Naomi; Yamasaki, Masahiro; Daido, Wakako; Ishiyama, Sayaka; Deguchi, Naoko; Taniwaki, Masaya
Abstract : Bronchial fibroepithelial polyps represent a rare type of tumour that displays endobronchial growth. The findings of these lesions on auto‐fluorescence imaging (AFI) bronchoscopy have not been reported, despite the usefulness of AFI in detecting early lung cancer. We report the case of a patient with a bronchial fibroepithelial polyp that displayed positivity (magenta colour) on AFI. The patient was a 65‐year‐old man, in whom an endobronchial polypoid lesion of 10 mm diameter had been detected in the right basal bronchus by chest computed tomography (CT). On bronchoscopic examination, we found a whitish, smooth polypoid lesion. The lesion appeared magenta on AFI. On CT, however, the lesion had been almost stable for 4 years and 4 months. Bronchial fibroepithelial polyps may show AFI positivity, even when the lesion displays benign behaviour. The diagnosis of the lesion should not be confused by AFI positivity, and unnecessary surgical intervention should be avoided. Abstract : Bronchial fibroepithelial polyps may display auto‐fluorescence imaging (AFI) positivity; however, the lesion displays benign behaviour. The diagnosis of bronchial fibroepithelial polyps should not be confused by AFI positivity, and unnecessary surgical intervention should be avoided.